Pengaruh kecerdasan emosional terhadap penilaian autentik di sekolah menengah atas - Gadink, Muhammad; Sukenti, Desi (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study aims to specifically explore the influence of emotional intelligence on the implementation of authentic assessment by Indonesian language teachers in Senior High Schools in Pekanbaru. The research was conducted to test the hypothesis that emotional intelligence positively correlates with the effectiveness of authentic assessment implementation. The method used is a quantitative approach with a survey design, where data were collected through a Likert scale questionnaire designed to measure emotional intelligence and authentic assessment practices. The research sample consists of 50 Indonesian language teachers selected using purposive sampling techniques. Data were analyzed using descriptive statistics to provide an overview of the sample characteristics, as well as linear regression analysis to examine the relationship between emotional intelligence and authentic assessment implementation. The results of this study indicate a significant positive correlation between emotional intelligence and the quality of authentic assessment conducted by teachers. Teachers with higher levels of emotional intelligence tend to be better at managing stress, understanding students' emotions, and collaborating effectively, which positively impacts the accuracy and quality of their assessments. This research is relevant in the educational context as it highlights the importance of emotional intelligence training in teacher development programs to enhance assessment practices and educational outcomes. These findings may influence educational policy by emphasizing the need for integrating emotional intelligence into teacher training curricula to improve the quality of assessments in schools.